2016
DOI: 10.1016/j.molcel.2016.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Damage Transducer RNF8 Facilitates Cancer Chemoresistance and Progression through Twist Activation

Abstract: Twist has been shown to cause treatment failure, cancer progression and cancer-related death. However, strategies that directly target Twist are not yet conceivable. Here we revealed K63-linked ubiquitination is a crucial regulatory mechanism for Twist activation. Through an E3 ligase screen and biochemical studies, we unexpectedly identified that RNF8 functions as a direct Twist activator by triggering K63-linked ubiquitination of Twist. RNF8-promoted Twist ubiquitination is required for Twist localization to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 57 publications
3
91
0
Order By: Relevance
“…Extensive work has established the vital role of K63-Ub pathway in Akt oncogenic signaling and IKK β /NF κ B inflammation pathways [119, 120]. A recent report revealed an essential role for nonproteolytic Ub pathway in Twist activation and Twist-mediated EMT and CSC acquisition [121], suggesting that targeting the controlling E3 ligases for K63-linked Ub of EMT-TFs can be a potential approach for development of EMT/CSC-based new cancer therapeutics. It remains elusive whether and how this K63-linked Ub governs protein activity of major EMT-TFs other than Twist.…”
Section: Strategies and Current Advances In Targeting Emt-tfsmentioning
confidence: 99%
“…Extensive work has established the vital role of K63-Ub pathway in Akt oncogenic signaling and IKK β /NF κ B inflammation pathways [119, 120]. A recent report revealed an essential role for nonproteolytic Ub pathway in Twist activation and Twist-mediated EMT and CSC acquisition [121], suggesting that targeting the controlling E3 ligases for K63-linked Ub of EMT-TFs can be a potential approach for development of EMT/CSC-based new cancer therapeutics. It remains elusive whether and how this K63-linked Ub governs protein activity of major EMT-TFs other than Twist.…”
Section: Strategies and Current Advances In Targeting Emt-tfsmentioning
confidence: 99%
“…Depletion of RNF8 retains Ku80 on DNA and impairs NHEJ e ciency [36]. Recent study found that RNF8 facilities doxorubicin resistance in cancer stem cells [37]and radiation resistance in nasopharyngeal cancer, bladder cancer [38,39]. These studies prompt us to investigate the role of RNF8 in NHEJ in EC.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Besides, DNA repair is closely coupled with cell survival. Weyemi et al 25 found that silencing H2A.X, an essential molecule involved in DNA repair, activated EMT transcription factors and increased tumor progression.…”
Section: Discussionmentioning
confidence: 99%